Analytical validation of a prognostic prostate cancer gene expression assay using formalin fixed paraffin embedded tissue - Paul Wallace Medlow; Christopher James Steele; Andrena Marie McCavigan; Wesley Reardon; Christopher Michael Brown; Shauna May Lambe; Felipe Augusto Andre Ishiy; Steven Michael Walker; Gemma Elizabeth Logan; Olaide Yaqeen Raji; Viktor Berge; Betina Katz; et al. (BMC Medical Genomics, 2018)
Abstract Background There is a clear need for assays that can predict the risk of metastatic prostate cancer following curative procedures. Importantly these assays must be analytically robust in order to provide quality data for important clinical decisions. DNA microarray based gene expression assays measure several analytes simultaneously and can present specific challenges to analytical validation. This study describes the analytical validation of one such assay designed to predict metastatic recurrence in prostate cancer using primary formalin fixed paraffin embedded tumour material. Methods Accuracy was evaluated with a method comparison study between the assay development platform (Prostate Disease Specific Array) and an alternative platform (Xcel™ microarray) using 50 formalin-fixed, paraffin-embedded prostate cancer patient samples. An additional 70 samples were used to establish the assay reportable range. Determination of assay precision and sensitivity was performed on multiple technical replicates of three prostate cancer samples across multiple variables (operators, days, runs, reagent lots, and equipment) and RNA/cDNA inputs respectively using the appropriate linear mixed model. Results The overall agreement between the development and alternative platform was 94.7% (95% confidence interval, 86.9–98.5%). The reportable range was determined to be 0.150 to 1.107 for core needle biopsy samples and − 0.214 to 0.844 for radical prostatectomy samples. From the precision study, the standard deviations for assay repeatability and reproducibility were 0.032 and 0.040 respectively. The sensitivity study demonstrated that a total RNA input and cDNA input of 50 ng and 3.5 μg respectively was conservative. Conclusion The Metastatic Assay was found to be highly reproducible and precise. In conclusion the studies demonstrated an acceptable analytical performance for the assay and support its potential use in the clinic.